Anatomical relationship between roots of maxillary posterior teeth and maxillary sinus using cone-beam computed tomography - Mamta Kaushik; Pratyasha Kaushik; Neha Mehra; Roshni Sharma; Elkanti Soujanya; Uday Kumar (Wolters Kluwer Medknow Publications, 2020)
Aim: Maxillary sinusitis of odontogenic origin accounts for approximately 10%-12% of maxillary sinusitis cases. The primary objective of the present study was to analyze the vertical relationship between the maxillary posterior roots and the adjacent maxillary sinus floor (MSF) in the Indian population using cone-beam computed tomography. The secondary objective was to correlate the data with age and gender. Materials and Methods: The shortest distance between 452 maxillary posterior teeth and the adjacent border of MSF was measured. The data were divided into three groups. Group IS included maxillary posterior teeth roots protruding into the sinus, Group CO included root apices contacting the MSF, and Group OS included root apices not contacting the MSF. The data obtained were correlated with age and gender. Results: The vertical distance of the root apices of second premolars from the MSF was significantly lesser compared to the root apices of first premolars (P < 0.05). The difference between the vertical distance of buccal roots and palatal roots (PRs) of first molar from the MSF was significantly more (P < 0.05). Majority of the roots of posterior teeth were located below the MSF border (Type OS). Type IS was most frequently seen for PRs of maxillary first molars (29.12%). The frequency of Type IS decreased with increasing age. The distance between the posterior root apices and the adjacent border of the MSF was found to be more in males compared to females. Conclusion: The PRs of maxillary first molars were found to be closest to the MSF. Variation in the vertical relationship was found by age and gender.